The Effect of Contextual Teaching And Learning (CTL) Learning Model on The Ability Of Concept Understanding Class VII Students of SMP 16, Kota Bengkulu - Sufianto Sufianto (Jurnal Pendidikan Matematika Raflesia, 2019)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) learning model on the ability to understand the concepts of class VII students of SMP 16 Kota Bengkulu. The research carried out was quasi-experimental with a population of all students in class VII of SMP 16 Kota Bengkulu totaling 218 students. Samples were taken by random sampling technique and a sample of 60 students was obtained, 30 students in the VIIA class as the experimental class, 30 students in the VIIE class as the control class. Data collection using Instrument concept understanding ability test. Data analysis techniques using Ancova. The results showed that there was the influence of the Contextual Teaching and Learning (CTL) learning model on the conceptual comprehension ability of seventh grade students in Bengkulu City 16 Junior High School at 80.50% with an average of 82.75 and there was an effect of an initial ability of 60.50% with an average average of 82.80. It can be concluded that the ability to understand students' concepts is better by using the Contextual Teaching and Learning (CTL) learning model.